comparative study of biomass and morpho-physiological traits for different deciduous species in semi-arid afforestation region of Mongolia - Tseepil Avirmed; Ser-Oddamba Byambadorj; Khaulenbek Akhmadi; Khulan Sharavdorj; Tsedensodnom Tsognemekh; Gerelbaatar Sukhbaatar; Batkhuu Nyam-Osor (Proceedings of the Mongolian Academy of Sciences)
Afforestation practices are useful tools for rehabilitating degraded lands in many parts of the world, as well as in Mongolia for protecting soil, water resources, and the potential of carbon sequestration to mitigate climate change. And so, regular investigation was conducted to determine the response and adaptation of Populus sibirica, Ulmus pumila, and Hippophae rhamnoides in terms of growth characteristics and leaf morpho-physiological traits to suggest and select effective and sustainable afforestation methods to suit Mongolia’s conditions. We measured the root collar diameter (RCD), height growth, leaf area (LA), speciﬁc leaf area (SLA), leaf biomass (LB), chlorophyll concentration and leaf water potential (ψ) of the selected species. Results showed that P. sibirica (135.3±6.81cm) height growth, stem, root and total biomass were higher among the studied species, but leaf and branch biomass was higher in U. pumila (93.46±5.10cm). However, leaf morphological parameters and chlorophyll content was higher for P. sibirica (330.56±56.81µg/ml) compared with other species. Leaf water potential was found lower for U. pumila and higher in H. rhamnoides. Therefore, we suggest that U. pumila is more adaptable to low mean annual precipitation regions, requiring less water and H. rhamnoides provide good financial source for local community as they yield fruits. Our ﬁndings are relevant to ensuring the sustainability of afforestation programs in semiarid conditions in Mongolia.